A stone in the lacrimal gland: a case report and literature review. (2nd January 2020) - Othman, Othmaliza Binti; Takahashi, Yasuhiro; Valencia, Ma. Regina Paula; Kakizaki, Hirohiko
ABSTRACT: A 59-year-old man presented with recurrent localized redness of the right eye for 3 months duration despite topical antibiotic and steroid administration. Examination revealed focal conjunctival injection in the temporal region and a palpable right lacrimal gland. During incisional biopsy, a small, white, hard mass was noted within the lacrimal gland, which was surgically removed. Histopathological examination revealed a lacrimal gland ductule stone. The conjunctival injection resolved immediately after surgery. A thorough review of literature was done, which yielded 19 cases of lacrimal gland stones reported in modern literature and these cases were reviewed.